The Routledge handbook of East Central and Eastern Europe in the Middle Ages, 500-1300
1 online resource.
Keywords: "The Routledge Handbook of East Central and Eastern Europe in the Middle Ages, 500-1300 is the first of its kind to provide a point of reference for the history of the whole of Eastern Europe during the Middle Ages. While historians have recognized the importance of integrating the eastern part of the European continent into surveys of the Middle Ages, few have actually paid attention to the region, its specific features, problems of chronology, and historiography. This vast region represents more than two thirds of the European continent, but its history in general - and its medieval history in particular - is poorly known. This book covers the history of the whole region, from the Balkans to the Carpathian Basin, and the Bohemian Forest to the Finnish Bay. It provides an overview of the current state of research and a route map for navigating an abundant historiography available in more than ten different languages. Chapters cover topics as diverse as religion, architecture, art, state formation, migration, law, trade, and the experiences of women and children. This book is an essential reference for scholars and students of medieval history, as well as those interested in the history of central and eastern Europe"--